Paediatric acute non-traumatic limp presenting to the emergency department: a retrospective observational study. Issue 3 (22nd November 2022) - Tu, Jacky; Haines, Mitchell; Gowdie, Peter; Craig, Simon
Abstract : Background: Acute non-traumatic limp in children has many causes, ranging from common benign and self-limiting disease to serious time-sensitive emergencies such as septic arthritis. We aimed to (1) describe the epidemiology and workup of paediatric acute non-traumatic limp presentation in three Australian EDs and (2) compare investigations and treatment between a tertiary paediatric centre and two non-tertiary centres. Methods: A retrospective chart review of children aged 0–16 years, with an initial presentation of non-traumatic limp to three EDs in Melbourne, Australia. Data on presentation, management and outcomes was systematically collected on all eligible patients. Results: Of 63 941 presentations over a 12-month period, 475 (0.7%) met inclusion criteria. The median (IQR) age of presentation was 5 (3–8) years, with a male predominance (61%). Blood tests and imaging were performed in 39% and 51%, respectively. 34% of presentations had no investigations. The most frequent ED diagnoses were transient synovitis (37%) and viral myositis (16%). 84% were discharged home after ED evaluation. Compared with the two non-tertiary hospitals, children who presented to the tertiary centre were less likely to have any investigation performed (OR=0.41, 95% CI: 0.27 to 0.62, p<0.001) and more likely to be discharged home after evaluation (OR=4.67, 95% CI: 2.79 to 7.81, p<0.001). Conclusion: Although mostly due to benign disorders, an important number of limping children who presented to the ED had serious disease, with approximately one-third of these not diagnosed at the initial ED visit. There is large variation in workup including blood test, imaging and decisions regarding ED disposition.